2020
DOI: 10.1002/anie.202013041
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Synthesis of Chiral Monohydrosilanes by Intramolecular C−H Functionalization of Dihydrosilanes

Abstract: The preparation of chiral monohydrosilanes remains a rarely achieved goal. To this end a Rh‐catalyzed desymmetrization of dihydrosilanes by way of intramolecular C(sp2)−H functionalization under simple and mild conditions has now been developed. This method provides easy access to a broad range of chiral monohydrosilanes in good yields with excellent enantioselectivities (up to >99 % ee). The resulting monohydrosilanes constitute a good platform to access stereogenic silicon compounds, as well as useful compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 76 publications
0
27
0
1
Order By: Relevance
“…Thea bsolute configuration of 2am was determined to be S based on single-crystal X-ray analysis (Scheme S1 in SI). [11] Isopropyl-Si substrates bearing substituents on both the A and the B rings were also compatible with the optimized reaction conditions (Scheme 3). In general, having substituents on both rings decreased the yields and enantioselectivities.Such an impact was very pronounced in the cases of 2ba, 2bh and 2bk.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Thea bsolute configuration of 2am was determined to be S based on single-crystal X-ray analysis (Scheme S1 in SI). [11] Isopropyl-Si substrates bearing substituents on both the A and the B rings were also compatible with the optimized reaction conditions (Scheme 3). In general, having substituents on both rings decreased the yields and enantioselectivities.Such an impact was very pronounced in the cases of 2ba, 2bh and 2bk.…”
Section: Resultsmentioning
confidence: 83%
“…We also examined the ferrocene substrates with Fsubstitutions on the A ring (e.g., 2el, 2em and 2en), which showed that the substitution on A ring were well tolerated with different alkyl-Si patterns.I tw as thus clear that our method should work well on various type of ferrocene substrates.T he absolute configuration of the product 2eg was determined to be RIS Si, R p according to single-crystal Xray analysis (Scheme S3 in SI). [11] Taken together, the reaction scope studies have demonstrated that our method can produce aw ide variety of chiral monohydrosilanes.T he reaction worked well on bi-phenyl skeletons,t olerating many types of substitution patterns on either phenyl ring or on the bi-phenyls (Scheme 2and 3). The substitutions the Si could be selected from at least 7different alkyl groups (Scheme 4).…”
Section: Forschungsartikelmentioning
confidence: 70%
See 1 more Smart Citation
“…Early this year, the asymmetric synthesis of chiral monohydrosilanes via Rh-catalyzed intramolecular CÀ H silylation approach has been finally realized by the group of W. He. [20] Using a combination of [Rh(COD)Cl] 2 and (R)-DTBM-Segphos (L6), a wide range of silicon-stereogenic spirosilabifluorenecored and ferrocene-based monohydrosilanes were readily obtained in high yields and excellent enantioselectivities under mild conditions (Scheme 7). Gratifyingly, silicon-stereogenic spirosilabifluorene-cored tetrasubstituted silanes could be obtained via stereospecific transformations of the SiÀ H bond, including alcoholysis with alcohol, hydrosilylation with ketone, alkene and alkyne, and dehydrogenative arylation with arene.…”
Section: Transition Metal-catalyzed Asymmetric Desymmetrization Of Prochiral Dihydrosilanesmentioning
confidence: 99%
“…Early this year, the asymmetric synthesis of chiral monohydrosilanes via Rh‐catalyzed intramolecular C−H silylation approach has been finally realized by the group of W. He [20] . Using a combination of [Rh(COD)Cl] 2 and ( R )‐DTBM‐Segphos ( L6 ), a wide range of silicon‐stereogenic spirosilabifluorene‐cored and ferrocene‐based monohydrosilanes were readily obtained in high yields and excellent enantioselectivities under mild conditions (Scheme 7).…”
Section: Transition Metal‐catalyzed Asymmetric Desymmetrization Of Prochiral Dihydrosilanesmentioning
confidence: 99%